Online health information and pediatric treatment decisions: a study of generation Y parents - Vieira , Danilo Marçal; Rondina, João Marcelo; Ribeiro Altrão Iorino, Luana; Santos , Emerson Roberto dos; Menezes, João Daniel De Souza; Souza, Doroteia Rossi da Silva; Caldas, Heloísa Cristina; Lima, Alba Regina de Abreu; Brienze , Vânia Maria Sabadoto; Werneck , Alexandre Lins; Fucuta , Patrícia da Silva; André, Júlio César (Acta Biomedica Atenei Parmensis, 2024)
Background and aim of the work: E-health has generated benefits and challenges, such as spreading false information online. This study investigated the impact of online health research on the treatment and diagnosis of children aged 0 to 12 whose guardians belong to Generation Y, examining interference in the doctor-patient relationship and the influence of socioeconomic factors. The practical implications of these findings are significant, as they can guide communication strategies, provide reliable information, and promote collaboration between professionals and patients. Methods: A descriptive cross-sectional study carried out in a hospital in the interior of São Paulo between 2022 and 2023. Participants aged 32 to 42, responsible for children aged 0 to 12, answered a questionnaire on health research habits. We performed the statistical analysis using descriptive statistics, Spearman's correlation, and the Mann-Whitney test. Results: Our sample of 101 participants was predominantly female (80.2%) and heterogeneous in age, marital status, skin color, schooling, and occupation. The use of cell phones to access the internet was predominant (100%), and 34% always searched for health information online. Most found the information understandable (51.4%) and valuable (58.6%) but were cautious about its reliability. We found correlations between demographic data and the importance of different sources. Conclusions: The study contributes to understanding online health information-seeking habits and behaviors.